2015
DOI: 10.1097/rlu.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic Accessory Spleen Mimicking Neuroendocrine Tumor on 68Ga-DOTATATE PET/CT

Abstract: Besides well-known physiologic uptake of Ga-DOTATATE in spleen, pituitary gland, pancreatic head, adrenals, kidney, and urinary bladder, sometimes unusual areas of uptake are found. We report a case of a 53-year-old woman who had vague pain in abdomen for which abdominal CT was done showing a contrast-enhancing lesion in the pancreatic tail. It was suspected to be of neuroendocrine origin and Ga-DOTATATE PET/CT showed a corresponding focal uptake. Spleen-preserving pancreatic tail resection was performed. Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…Для уточнения диагноза необходимо выполнение МРТ, а в отдельных случаях и тонкоигольной биопсии под контролем УЗИ. При МРТ измеряемые коэффициенты диффузии ДС и основного органа совпадают [5][6][7][8][9].…”
Section: Discussionunclassified
“…Для уточнения диагноза необходимо выполнение МРТ, а в отдельных случаях и тонкоигольной биопсии под контролем УЗИ. При МРТ измеряемые коэффициенты диффузии ДС и основного органа совпадают [5][6][7][8][9].…”
Section: Discussionunclassified
“…Literature documents many case reports of false positives on PET-CT NETSPOT due to ectopic splenic anomalies [12][13][14][15][16][17]. One case report with a literature review showed that 66.7% of patients with intrapancreatic accessory spleen ended up undergoing unnecessary pancreatic resections [13].…”
Section: Discussionmentioning
confidence: 99%
“…The second case was a patient previously splenectomised for trauma that had a second trauma with an injured accessory spleen; in this case, the diagnosis was made on CT scan. Thirteen patients in our study underwent CT scan for diagnosis; in addition, other different diagnostic methods, including US [36], MRI [37] and PET [38] were used. One patient underwent only US, and another underwent only MRI.…”
Section: Discussionmentioning
confidence: 99%